Tutela efetiva: sistemática e positivação - Guimarães, José Lázaro Alfredo (2006)
In this work I analyze, from the beginning to the end of procedural relations, the practical results of judicial decisions, mainly their subjective and binding effects. I argue that anticipated effects of Judicial Protection in spite of its intense use and consequent surcharging of courts remains a very important tool. Although Class Action is the best way to achieve, social results, some restrictions in the law threat the fulfillment of the constitutional principle concerning public civil action and consumer protection. The overcoming of obstacles in Judiciary procedures challenges judges to apply extensively their duties in conducting trials according to the rule of reasonable length which is guaranteed in Brazilian Constitution, and so far by effective tutelage.